Putting the private sector at the centre of climate-smart agriculture - Gordon, Una May; Were, Thomas Obiero; Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief draws on three cases to show how the private sector contributes to the conceptualisation, design, delivery and evaluation of climate-smart agricultural interventions and can help bring them to scale. Engaging the private sector in CSA interventions enhances the applicability – and thus the sustainability of interventions, increases uptake and delivers a triple win for donors, beneficiaries and the private sector. They emphasise that private-sector players will be more likely to engage in scaling-up of CSA when they can see a compelling business case to justify their investments.